Historical and archaeological aspects of Egyptian funerary culture : religious ideas and ritual practice in Middle Kingdom elite cemeteries - Willems, Harco. (Culture and History of the Ancient Near East, 2014)
Historical and Archaeological Aspects of Egyptian Funerary Culture , a thoroughly reworked translation of Les textes des sarcophages et la démocratie published in 2008, challenges the widespread idea that the "royal" Pyramid Texts of the Old Kingdom after a process of "democratisation" became, in the Middle Kingdom, accessible even to the average Egyptian in the form of the Coffin Texts. Rather they remained an element of elite funerary culture, and particularly so in the Upper Egyptian nomes. The author traces the emergence here of the so-called "nomarchs" and their survival in the Middle Kingdom. The site of Dayr al-Barshā, currently under excavation, shows how nomarch cemeteries could even develop into large-scale processional landscapes intended for the cult of the local ruler. This book also provides an updated list of the hundreds of (mostly unpublished) Middle Kingdom coffins and proposes a new reference system for these.